LINGUISTIC STUDY OF WORD CATEGORIES IN FRENCH AND UZBEK LANGUAGES (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article presents and treats the theoretical perspectives of linguists in the framework of the linguistic study of speech categories within the framework of French and Uzbek languages. At the same time, the examples were weighed down for analysis, final conclusions were reached. Differences and differences of speech categories within the framework of two disparate languages are cited on the basis of examples.